Positivity of solution of nonhomogeneous stochastic differential equation with non-Lipschitz diffusion - Mishura, Y.; Posashkova, S. (Інститут математики НАН України, 2008)
We give a sufficient condition on coefficients of a nonhomogeneous stochastic differential equation with non-Lipschitz diffusion for a solution starting from arbitrary nonrandom positive point to stay positive. Some examples of application of the condition mentioned above are considered.